Sustainable care for children with cancer: a Lancet Oncology Commission. Issue 4 (April 2020) - Atun, Rifat; Bhakta, Nickhill; Denburg, Avram; Frazier, A Lindsay; Friedrich, Paola; Gupta, Sumit; Lam, Catherine G; Ward, Zachary J; Yeh, Jennifer M; Allemani, Claudia; Coleman, Michel P; Di Carlo, Veronica; et al.
Summary: We estimate that there will be 13·7 million new cases of childhood cancer globally between 2020 and 2050. At current levels of health system performance (including access and referral), 6·1 million (44·9%) of these children will be undiagnosed. Between 2020 and 2050, 11·1 million children will die from cancer if no additional investments are made to improve access to health-care services or childhood cancer treatment. Of this total, 9·3 million children (84·1%) will be in low-income and lower-middle-income countries. This burden could be vastly reduced with new funding to scale up cost-effective interventions. Simultaneous comprehensive scale-up of interventions could avert 6·2 million deaths in children with cancer in this period, more than half (56·1%) of the total number of deaths otherwise projected. Taking excess mortality risk into consideration, this reduction in the number of deaths is projected to produce a gain of 318 million life-years. In addition, the global lifetime productivity gains of US2580 billion in 2020–50 would be four times greater than the cumulative treatment costs of 594 billion, producing a net benefit of 1986 billion on the global investment: a net return of 3 for every 1 invested. In sum, the burden of childhood cancer, which has been grossly underestimated in the past, can be effectively diminished to realise massive health and economic benefits and to avert millions of needless deaths.